(untitled) (Research, Society and Development, 2022)
Some parasites are common in dogs and cats and cause zoonoses through direct or indirect contact with feces, such as fungi, helminths and protozoa. This study aimed to identify enteric parasites in fecal samples from cats (Felis catus) collected on the Campus of the Universidade Federal de Rondônia, in Porto Velho, Rondônia, to investigate possible exposure to endemic zoonoses for epidemic control. Starting from an experimental study with a quantitative-qualitative approach, twelve samples were collected in June 2021 and May 2022, dispersed in the Campus, preserved in formalin and sent to the Histoanalysis laboratory from UNIR. The parasitic analyzes of feces were performed using the methods of Hoffman and Willis. By analyzing the samples under optical microscopy, it was possible to identify, morphologically, helminths such as Trichuris trichiura, Opisthorchis spp., Ancylostomidae, Strongyloides stercoralis, Ascaris lumbricoides, Enterobius vermicularis, Toxocara cati and Hymenolepis sp., rhabditoid and filarioid larvae of S. stercoralis, and protozoa such as Toxoplasma gondii, Balantidium coli and Sarcoptes spp. S. stercoralis was observed with the highest incidence followed by Ancylostoma sp. and the one with the greatest zoonotic potential is T. gondii. The data show a high incidence of parasites in the feces of these felines, which can infect not only academics but also animals of the most diverse species that inhabit the rural ecosystem of the University. Thus, urgent measures are needed to combat the abandonment of these animals on Campus and how they will be treated to control gastrointestinal parasites.